Increase in TGF-β secreting CD4⁺CD25⁺ FOXP3⁺ T regulatory cells in anergic lepromatous leprosy patients. - Chaman Saini; Venkatesh Ramesh; Indira Nath (Public Library of Science (PLoS), 2014)
BACKGROUND: Lepromatous leprosy caused by Mycobacterium leprae is associated with antigen specific T cell unresponsiveness/anergy whose underlying mechanisms are not fully defined. We investigated the role of CD25(+)FOXP3(+) regulatory T cells in both skin lesions and M.leprae stimulated PBMC cultures of 28 each of freshly diagnosed patients with borderline tuberculoid (BT) and lepromatous leprosy (LL) as well as 7 healthy household contacts of leprosy patients and 4 normal skin samples. METHODOLOGY/PRINCIPLE FINDINGS: Quantitative reverse transcribed PCR (qPCR), immuno-histochemistry/flowcytometry and ELISA were used respectively for gene expression, phenotype characterization and cytokine levels in PBMC culture supernatants. Both skin lesions as well as in vitro antigen stimulated PBMC showed increased percentage/mean fluorescence intensity of cells and higher gene expression for FOXP3(+), TGF-β in lepromatous (p<0.01) as compared to tuberculoid leprosy patients. CD4(+)CD25(+)FOXP3(+) T cells (Tregs) were increased in unstimulated basal cultures (p<0.0003) and showed further increase in in vitro antigen but not mitogen (phytohemaglutinin) stimulated PBMC (iTreg) in lepromatous as compared to tuberculoid leprosy patients (p<0.002). iTregs of lepromatous patients showed intracellular TGF-β which was further confirmed by increase in TGF-β in culture supernatants (p<0.003). Furthermore, TGF-β in iTreg cells was associated with phosphorylation of STAT5A. TGF-β was seen in CD25(+) cells of the CD4(+) but not that of CD8(+) T cell lineage in leprosy patients. iTregs did not show intracellular IFN-γ or IL-17 in lepromatous leprosy patients. CONCLUSIONS/SIGNIFICANCE: Our results indicate that FOXP3(+) iTregs with TGF-β may down regulate T cell responses leading to the antigen specific anergy associated with lepromatous leprosy.